Determinants of the Implementation of Participatory Actions in the Environmental Education with Children and Adolescents in Chile - Rojas-Andrade, R; Prosser-Bravo, G (Routledge, 2024)
Internationally, academics and social organizations have emphasized the incorporation of the perspective of children and adolescents in the design, evaluation, and execution of environmental education activities. This study sought to identify those contextual factors that influence the implementation of participatory actions in environmental education. An online survey was applied to 78 teachers, non-formal educators, administrators, researchers and journalists involved in environmental education. Through thematic content analysis, 17 determinants of implementation were identified, highlighting the traditional education model, cultural patterns, willing and social support, time, resources, and organizational drivers. It is argued that beyond macro and meso structural conditions, the implementation of these actions falls on a greater measure in the self-efficacy of the people involved in education, as well as in their possibility to manage the implementation conditions and obstacles. © 2023 Informa UK Limited, trading as Taylor & Francis Group.